2020
DOI: 10.1186/s40985-020-00138-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cohousing model on people’s health and wellbeing: a scoping review

Abstract: Background Housing is a social determinant of health. Extensive research has highlighted its adverse effects on health. However, less is known about the effects of cohousing typology on health, which has the potential to create lively social networks and healthy communities and environments. We report the findings of a scoping study designed to gather and synthesise all known evidence on the relationship between cohousing and wellbeing and health. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
(208 reference statements)
1
11
0
Order By: Relevance
“…Finally, does the association between housing problems and the mental health of single-person households differ from that of non-single-person households? The literature suggests that living with someone else is conducive to seniors’ mental health [ 43 , 44 ], but little is known about how it affects young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, does the association between housing problems and the mental health of single-person households differ from that of non-single-person households? The literature suggests that living with someone else is conducive to seniors’ mental health [ 43 , 44 ], but little is known about how it affects young adults.…”
Section: Introductionmentioning
confidence: 99%
“…The green buildings studies assessed a range of health outcomes, including communicable disease (associated with water systems, vector-borne disease), allergens and air quality (Allen et al 2015;Houghton & Castillo-Salgado 2017, 2019. The building type studies Impacts of exposure on thermal control in the elderly and those with respiratory conditions (Jevons et al 2016); cardio-respiratory, paediatric, maternal outcomes and mortality (Lee et al 2020a;Katoto et al 2019) Interventions to reduce exposure and general health benefits to children and adults (Quansah et al 2017;Bailey et al 2019) Environmental equity (Bailey et al 2019); air pollution (PM) (Katoto et al 2019;Quansah et al 2017 Impacts of conditions on: social wellbeing, QoL and mental health (Barros et al 2019;Carrere et al 2020;Cho et al 2016;Garin et al 2014); sedentary lifestyles (Chastin et al 2015); falls and mortality (Cho et al 2016); infectious diseases and maternal outcomes (Heijnen et al 2014) Efficient use of resources (Barros et al 2019) Outdoor space (e.g. gardens, outdoor equipment)…”
Section: Dwelling Designmentioning
confidence: 99%
“…Interventions to improve the physical activity of children (Carlin et al 2017 reported on physical space and mental health and wellbeing (Barros et al 2019;Garin et al 2014), the impact of accessible design on falls and mental health (Cho et al 2016), and how design can minimise risks of injury, particularly later in life (Garin et al 2014); sedentary lifestyles associated with apartment or duplex living (Chastin et al 2015); physical and mental health, and wellbeing (Carrere et al 2020); and shared sanitation's impact on communicable disease (Heijnen et al 2014). Two studies looked at health impacts associated with a dwelling's outdoor space, including one on the physical activity benefits of gardens and outdoor equipment for children (Carlin et al 2017), and one on stress and time spent gardening (Kondo et al 2018b).…”
Section: Dwelling Designmentioning
confidence: 99%
“…While there are exceptions (for instance [17]) in which the authors find greater levels of social capital in community-led co-operatives in comparison with that found in housing developments created and managed by others,-a note of caution should be sounded on the definition of different models. In one scoping review, [26] the authors note that there remains no consensus on definitions, in part a reflection of the complexity of different models and terms in use across different countries. These definitional issues are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…These definitional issues are discussed below. Notwithstanding this, the primary finding of both the research noted above [26] and another similar scoping review [27] was that there remains a dearth of empirical data beyond individual case studies, in particular those making comparisons with non-cohousing samples, or larger-scale quantitative studies.…”
Section: Introductionmentioning
confidence: 99%